Impact of technical barriers to trade on sulfur dioxide and nitrogen oxide emissions in China's manufacturing sector - Liu, Hongping (2024)
This study examines the impact of technical barriers to trade (TBT) on air pollution levels within China, utilizing a robust dataset from the Enterprise-Level Pollution Emission Database and the Customs database, covering the period from 2002 to 2013. A two-way fixed effects econometric model is employed to rigorously assess the relationship between TBT and air pollutant emission intensities in Chinese industrial firms. Our findings reveal a definitive correlation between increased TBT and elevated emission levels of key pollutants. Specifically, each 1% increase in TBT correlates with rises in emission intensities: 0.025% for sulfur dioxide (SO2), 0.024% for soot, 0.076% for industrial dust, and 0.012% for nitrogen oxides (NOx). The analysis highlights that restrictions on imported intermediates, as opposed to final goods, are primarily responsible for these increased emissions. This research underlines the critical environmental implications of trade policies and advocates for a balanced approach to promoting environmental health through the strategic importation of eco-friendly products and technologies.